2018
DOI: 10.1111/resp.13252
|View full text |Cite
|
Sign up to set email alerts
|

Success rate of medical thoracoscopy and talc pleurodesis in malignant pleurisy: A single‐centre experience

Abstract: The success rate of pleurodesis in malignant pleurisy could potentially be enhanced by correct patient selection and early referral for pleurodesis. Ultrasonic assessment of pleural adhesions and potential lung expansion prior to pleurodesis is useful in clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 16 publications
2
20
0
1
Order By: Relevance
“…The phenomenon was explained by a better transmission of heart beats through the atelectatic lung. The lung pulse has also been observed in the M-mode chest ultrasonography in patients with pleural effusion and atelectatic lung [4][5][6][7]. On the basis of our observations, we propose that pleural manometry could be a more sensitive and more accurate measure of pleural pulsations, albeit more invasive, than the M-mode US imaging.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The phenomenon was explained by a better transmission of heart beats through the atelectatic lung. The lung pulse has also been observed in the M-mode chest ultrasonography in patients with pleural effusion and atelectatic lung [4][5][6][7]. On the basis of our observations, we propose that pleural manometry could be a more sensitive and more accurate measure of pleural pulsations, albeit more invasive, than the M-mode US imaging.…”
Section: Discussionsupporting
confidence: 60%
“…It has been demonstrated that heart cyclic contractions generate blood flow in large vessels and can also interact with adjacent organs by passing on pulsations. This is exemplified by the so-called "lung pulse" which was first described as an early ultrasound sign of complete lung atelectasis [3], and later, also reported in patients with pleural effusion [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Published in Respirology , Leemans et al . conducted a retrospective responder analysis of 155 patients who underwent TP via medical thoracoscopy . Their success rate was in keeping with previous studies at 78%.…”
Section: Pleural Diseasementioning
confidence: 64%
“…In an earlier retrospective study, Leemans et al . reported similar adverse survival (median OS: 66 vs 169 days) in patients with MPE (due to a range of tumour types) who failed thoracoscopic talc pleurodesis due to NEL . In MPM, visceral pleural tumour, a frequent cause of NEL, has historically been associated with adverse survival via higher disease stage .…”
Section: Discussionmentioning
confidence: 87%